IMPACT OF INFORMATION SERVICES USING MEDIA FILM TO STUDENT MOTIVATION LEARNING AT SMA NEGERI 1 RAMAN UTARA, LAMPUNG TIMUR - Suciana, Septazema; Atieka, Nurul (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2014)
Abstract: One of the factors that can influence student learning is the motivation to learn. Students' motivation can be built with an understanding to students about the importance of learning how to learn effectively, and how to overcome learning problems. Departing from this, the research problem is formulated as follows: Is there any influence of information services on the students motivation ?. The aim of research to determine the effect of information services on the students motivation. The study design was one group pretest-posttest design. Subjects numbered 20 students. To determine the study subjects used the technique Proportionate Stratified Random Sampling.Hasil hypothesis test showed the value of t = 8.75> 1.729. The conclusion of the study is an information service that executed can affect motivation. Therefore, it is advisable to guidance and counseling teachers use information services by using the medium of film, so that the services effectively organized and able to enhance students' motivation.Keyword: Information Services, Motivation